2SPD-038 How long do hospital pharmacists spend in managing medicines shortages?. (March 2019) - Tribaudeau, L; Labat, V; Danet, C; Davasse, M; Rouanet, A; Degui, E; Guitart, C; Jammes, A; Cestac, P; Pecani, D; Bourdoncle, M
Abstract : Background: The incidence of medicines shortages has increased during the past few years. In Europe, most of the hospital pharmacists estimate that they spend at least 5 hours (h) per week dealing with shortages. Purpose: The objective was to quantify the time dedicated to managing shortages. Material and methods: A prospective study was conducted in a university hospital over two three-week periods in 2018. Each person from the supply and purchasing staff collected the daily time dedicated to managing shortages. The following data was collected: medicines affected, staff qualifications, supply shortage types and action taken. Results: The average time devoted to shortages was 6.6 hour per day (min=2.6 – max=12.1). The supply staff dedicated 5.4 hour per day (2.2–11.3): 2.1 hour for monitoring, 1.0 hour for meetings, 0.5 hour to update shortage tracking files, 0.5 hour for software settings, 0.4 hour to follow-up existing orders, 0.4 hour for order adjustments, 0.3 hour for writing information notes designed to professionals working in clinical units and 0.2 hour for shortage-suppliers lists analysis. The purchasing staff dedicated 1.2 hour per day (0.2–3.4): 0.4 hour for shortage analysis, 0.4 hour for solution research, 0.3 hour for alternative medicine market creation and 0.1 hour for closing shortage files. The overall time allocation was 33% for pharmacy residents, 31% for pharmacy technicians, 27% for pharmacists, 6% for administrative agents and 3% for pharmacy students. The mean time per shortage was 0.7 hour: 0.7 hour per shortage with quotas that needed medical validation, 0.6 hour per shortage with equivalent medicine and per shortage which implied stock monitoring, 0.5 hour per shortage with supply quotas and per shortage with near equivalent medicine, and 0.3 hour per shortage without alternative. Conclusion: These results may have been underestimated because of difficulties in data collection and because the time spent by clinical pharmacists was not implemented. However, this study shows precisely the time spent in managing shortages and will be useful in staff organisations as shortages are increasing. References and/or acknowledgements: 1. PGEU. Statement: Medicine Shortages in European Community Pharmacies 2012. (cited 15 October 2018). www.pgeu.eu/en/policy/20-medicine-shortages.html 2. Medicines shortages in European hospitals. Eur J Hosp Pharm 2014. (cited 15 October 2018]. www.eahp.eu/sites/default/files/shortages_report05online.pdf No conflict of interest.